Mechanical load regulates bone growth via periosteal Osteocrin - Watanabe-Takano, Haruko; Ochi, Hiroki; Chiba, Ayano; Matsuo, Ayaka; Kanai, Yugo; Fukuhara, Shigetomo; Ito, Naoki; Sako, Keisuke; Miyazaki, Takahiro; Tainaka, Kazuki; Harada, Ichiro; Sato, Shingo; et al. (Cell reports (Cambridge), 2021)
Mechanical stimuli including loading after birth promote bone growth. However, little is known about how mechanical force triggers biochemical signals to regulate bone growth. Here, we identified a periosteal-osteoblast-derived secretory peptide, Osteocrin (OSTN), as a mechanotransducer involved in load-induced long bone growth. OSTN produced by periosteal osteoblasts regulates growth plate growth by enhancing C-type natriuretic peptide (CNP)-dependent proliferation and maturation of chondrocytes, leading to elongation of long bones. Additionally, OSTN cooperates with CNP to regulate bone formation. CNP stimulates osteogenic differentiation of periosteal osteoprogenitors to induce bone formation. OSTN binds to natriuretic peptide receptor 3 (NPR3) in periosteal osteoprogenitors, thereby preventing NPR3-mediated clearance of CNP and consequently facilitating CNP-signal-mediated bone growth. Importantly, physiological loading induces Ostn expression in periosteal osteoblasts by suppressing Forkhead box protein O1 (FoxO1) transcription factor. Thus, this study reveals a crucial role of OSTN as a mechanotransducer converting mechanical loading to CNP-dependent bone formation. [Display omitted] •OSTN from periosteum regulates endochondral and intramembranous ossification•OSTN enhances osteogenesis through potentiation of CNP signaling•FoxO1 suppresses periosteal expression of OSTN under unloading condition•OSTN is required for physiological load-induced bone gain Watanabe-Takano et al. demonstrate that physiological loading induces Osteocrin (OSTN) expression in the periosteal osteoblasts of long bones through suppression of the Forkhead box protein O1 transcription factor. OSTN promotes bone growth through enhancement of C-type natriuretic peptide signaling, leading to elongation and appositional growth of long bones.